The varied functions of aluminium-activated malate transporters–much more than aluminium resistance. (9th June 2016) - Palmer, Antony J.; Baker, Alison; Muench, Stephen P.
Abstract : The ALMT (aluminium-activated malate transporter) family comprises a functionally diverse but structurally similar group of ion channels. They are found ubiquitously in plant species, expressed throughout different tissues, and located in either the plasma membrane or tonoplast. The first family member identified was Ta ALMT1, discovered in wheat root tips, which was found to be involved in aluminium resistance by means of malate exudation into the soil. However, since this discovery other family members have been shown to have many other functions such as roles in stomatal opening, general anionic homoeostasis, and in economically valuable traits such as fruit flavour. Recent evidence has also shown that ALMT proteins can act as key molecular actors in GABA (γ-aminobutyric acid) signalling, the first evidence that GABA can act as a signal transducer in plants.